2018
DOI: 10.1096/fj.201800716
|View full text |Cite
|
Sign up to set email alerts
|

The proteobacterial species Burkholderia pseudomallei produces ergothioneine, which enhances virulence in mammalian infection

Abstract: Bacteria use various endogenous antioxidants for protection against oxidative stress associated with environmental survival or host infection. Although glutathione (GSH) is the most abundant and widely used antioxidant in Proteobacteria, ergothioneine (EGT) is another microbial antioxidant, mainly produced by fungi and Actinobacteria. The Burkholderia genus is found in diverse environmental niches. We observed that gene homologs required for the synthesis of EGT are widely distributed throughout the genus. By … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 35 publications
3
27
0
Order By: Relevance
“…We have previously described the crystal structure of Cth EgtB and shown that this type of bacterial sulfoxide synthase accepts TMH and Cys as substrates . At neutral pH and at room temperature, Cth EgtB produces sulfoxide 3 as the main product (80 %) and cysteine dioxide as a minor product ( 6 , 20 %, Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously described the crystal structure of Cth EgtB and shown that this type of bacterial sulfoxide synthase accepts TMH and Cys as substrates . At neutral pH and at room temperature, Cth EgtB produces sulfoxide 3 as the main product (80 %) and cysteine dioxide as a minor product ( 6 , 20 %, Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…One of the most prominent of the ET-synthesising microorganisms is the pathogen, Mycobacterium tuberculosis, the causative agent of human tuberculosis [24, 97,98]. Indeed, inhibitors of the ET biosynthetic pathway (which should be a feasible therapeutic approach since this pathway does not occur in humans) could be a potential source of novel drugs to attack this and other pathogenic ET-synthesising organisms, such as that causing melioidosis [99]. One possibility is that M. tuberculosis not only makes ET but can also take it up from the environment (we have found that several bacteria can do this; our unpublished data); if the injury to the infected lung was to raise ET content in lung tissue (Fig.…”
Section: Conclusion and Possible Caveatsmentioning
confidence: 99%
“…From the properties of this molecule in vitro , antioxidant effects seem likely. However, other protective mechanisms may exist , and more work is required to elucidate them.…”
Section: Conclusion and Possible Caveatsmentioning
confidence: 99%
“…[ [146] , [147] , [148] ] and Burkholderia spp. [ 149 ] belonging to the phyla Actinobacteria and Proteobacteria, respectively. They produce ET from histidine, albeit through distinct mechanisms [ 150 ].…”
Section: Sources Of Ergothioneinementioning
confidence: 99%